EP491 Retrospective review of sentinel lymph node mapping in endometrial cancer using indocyanine green and near infra-red fluorescence imaging during minimally invasive surgery- mater hospital experience. (1st November 2019) - Chaowawanit, W; Campbell, V; Wilson, E; Chetty, N; Perrin, L; Jagasia, N; Barry, S
Abstract : Introduction/Background: Sentinel lymph node (SLN) mapping in endometrial cancer allows us to obtain the lymph node status for prescribing adjuvant therapies and avoids the morbidity of systematic lymphadenectomy. The aim of this study is to determine the feasibility of sentinel lymph node (SLN) mapping in early endometrial cancer. Methodology: All women with histologically confirmed endometrial cancer, treated with a minimally invasive hysterectomy, bilateral salpingo-oophorectomy and SLN mapping were included. All mapped SLNs were histopathological confirmed. Results: From January 2017 to April 2019, 138 patients met the inclusion criteria. Eighteen patients were excluded because of unexpected advanced disease, anatomical issues and incomplete medical records. One hundred twenty patients were analysed. A mean age was 62 years old with standard deviation (SD) 11 years and mean Body mass index (BMI) was 33.4 kg/m 2 (SD 7.4). The overall and bilateral SLN detection rates were 85.8% (103/120) and 72.5% (87/120), respectively. BMI <30 kg/m 2 was a significant predictor of successful detection. 50% of SLNs were detected in the external iliac region, while 15% were found outside the routine lymphadenectomy zone including common iliac, parametrial, infra-mesenteric para-aortic and presacral lymph nodes. Seven patients (5.8%) had positive SLNs. Conclusion: SLN mapping can reliably detect the SLN in early-stage endometrial cancer. Additionally, some patients having an uncommon site of lymph node metastasis might be missed without SLN mapping. Disclosure: Nothing to disclose.